Global Cities and The Future of Demographic Transformation - İskender Güneş (Sosyal Siyaset Konferansları Dergisi)
The structural transformation adventure of urbanization in global cities is always closely linked to economic development. Today, thanks to the demographic transformation that includes this economic situation, migrants have started to spread to small and medium-sized cities and global cities with less capacity and resources. In this process, the attitude of city administrations can balance the demographic change that occurs and the opportunities and costs that may be created by a wave of immigration. At the same time, it is important for cities to be prepared for possible situations by having future plans in place, to shape the future of both cities and their demographic structure in a positive sense. Although national legislation can regulate cross-border migration, concepts that can reveal the effects of migration on cities are needed. Among these, countries with weaknesses in areas such as city planning, financing and management, land allocation, housing supply, and basic services fall short of controlling migration flow and demographic planning. In addition, population changes that change and shape the demographic structure of cities on a global scale should be handled within this framework. Planning to be made on a global scale and with a holistic perspective will help each city shape its expectations about its future visually.